Benzaldehyde‐Promoted (Auto)Photocatalysis under Visible Light: Pitfalls and Opportunities in Photocatalytic H2O2 Production. Issue 3 (13th January 2023) - Krivtsov, Igor; Vazirani, Ashish; Mitoraj, Dariusz; Beranek, Radim
Abstract: Selective photooxidation of aromatic alcohols to corresponding aldehydes is a widely used model reaction for evaluation of performance of heterogeneous photocatalysts. A top example is the photocatalytic production of hydrogen peroxide via reduction of dioxygen with concomitant photooxidation of benzyl alcohol to benzaldehyde. Herein we demonstrate the ability of benzaldehyde to promote the auto‐photocatalytic oxidation of benzyl alcohol and produce large quantities of H2 O2 in solvent‐free (no water) or biphasic (with water) systems even under nominally visible (>420 nm cut‐off filter) light irradiation. These results shed critical light on the plethora of research reports on photocatalytic H2 O2 production in which benzyl alcohol was employed as electron donor. Since the autocatalytic pathway based on the photocatalytic activity of benzaldehyde formed during photocatalysis under such conditions cannot be neglected, the interpretations of photocatalytic performance are likely contentious and distorted in such reports. The use of benzyl alcohol as a model electron donor in photocatalytic studies should be therefore definitely discouraged. On the other hand, as we found that benzaldehyde‐mediated photocatalysis of H2 O2 production proceeds also using alternative electron donors ( e. g ., ethanol), our results highlight the possible prospects for a more general use of benzaldehyde and other aromatic aldehydes in visible light‐driven photocatalysis. Abstract : Photocatalytic H2 O2 production : This work sheds critical light on the use of benzyl alcohol as a model electron donor in studies of photocatalytic H2 O2 production via oxygen reduction by demonstrating the ability of benzaldehyde to promote auto‐photocatalytic oxidation of benzyl alcohol and produce large quantities of H2 O2 even under visible light irradiation.